2018
DOI: 10.15562/ism.v9i1.165
|View full text |Cite
|
Sign up to set email alerts
|

Gambaran stadium dan jenis histopatologi kanker payudara di Subbagian Bedah Onkologi RSUP Sanglah Denpasar tahun 2015-2016

Abstract: Background: Breast cancer is a malignant neoplasm disease where in parekim tissue there is abnormal breast tissue growth that is infiltrative and destructive and can metastatic. The high incidence of breast cancer in Indonesia, is not always followed by determination of clinical staging and histopathology completely, whereas clinical staging and histopathology is needed to determine diagnosis and further management. Knowledge of the staging and histopathology is also an important indicator in determining the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 1 publication
0
2
1
1
Order By: Relevance
“…Patients with metastatic breast cancer have a median survival rate of only 22 months after treatment [37] The most common histopathological type was invasive carcinoma of no special type grade 2namely 45 (38.8%), and the second most was Invasive carcinoma of no special type grade 3, namely 44 (37.9%) people. This result is different from the research conducted by Diahpradnya (2018) at Sanglah Hospital Denpasar of the 514 patients with the most invasive ductal carcinoma type, namely 61 people (84.7%) while the results in the study of Satya et al in 2015-2016 found that invasive ductal carcinoma the most, namely 483 (84%) people, invasive lobular carcinoma type as many as 61 people (10.60%) [5,6]. In research, Hartaningsih also found 81.9% with the histopathological classification of invasive ductal carcinoma [38].…”
Section: Introductioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Patients with metastatic breast cancer have a median survival rate of only 22 months after treatment [37] The most common histopathological type was invasive carcinoma of no special type grade 2namely 45 (38.8%), and the second most was Invasive carcinoma of no special type grade 3, namely 44 (37.9%) people. This result is different from the research conducted by Diahpradnya (2018) at Sanglah Hospital Denpasar of the 514 patients with the most invasive ductal carcinoma type, namely 61 people (84.7%) while the results in the study of Satya et al in 2015-2016 found that invasive ductal carcinoma the most, namely 483 (84%) people, invasive lobular carcinoma type as many as 61 people (10.60%) [5,6]. In research, Hartaningsih also found 81.9% with the histopathological classification of invasive ductal carcinoma [38].…”
Section: Introductioncontrasting
confidence: 56%
“…In 2016 of 322 patients, 11.81% had invasive lobular carcinoma histopathology, and 4.65% were different types of carcinoma. [6] According to research by Komang Trisna Aryawan et al in 2018 at Sanglah Hospital Denpasar, the highest number of subtypes was triple negative, with patients aged 41-50 years. [7] From these data, it is necessary to conduct research on breast cancer at the Sanjiwani Hospital, Gianyar, to provide public information, education, and counseling.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the stage, stage IV is known to have a total of 10 patients (34.5%). This is also found in research (Wangsa et al, 2018): late stages have a proportion of 45-55%; this high rate is due to awareness about breast health and a lack of early detection programs.…”
Section: Respondent Characteristicsmentioning
confidence: 53%
“…Biopsy results can be used for the diagnosis of breast cancer and determining the success of the given therapies. 3 Apart from histopathological examination, there is another classification system based on immunohistochemistry test in which the examination procedure uses antibodies as probes to detect antigens in tissue sections or other forms of cell preparations. Through immunohistochemistry examination, the subtype of breast cancer can be identified.…”
Section: Introductionmentioning
confidence: 99%